2023
DOI: 10.1039/d3ta03434h
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the local structure evolution and thermophysical properties of NaCl–KCl–MgCl2–LaCl3 melt driven by machine learning

Jia Zhao,
Taixi Feng,
Guimin Lu
et al.

Abstract: The local structure evolution and thermophysical properties of the NaCl–KCl–MgCl2–LaCl3 melt were thoroughly understood, which facilitates the advancement and innovation of molten salt electrolytic production for Mg–La alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Zhao et al studied the structure of molten NaCl–KCl–MgCl 2 –LaCl 3 mixtures using machine learning molecular dynamics (MD) and found that what they referred to as “La 3+ clusters” were disrupted with increasing MgCl 2 concentration. 54 Whereas this is likely, we make the case that MgCl 2 is very different from NaCl and not a spacer salt.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al studied the structure of molten NaCl–KCl–MgCl 2 –LaCl 3 mixtures using machine learning molecular dynamics (MD) and found that what they referred to as “La 3+ clusters” were disrupted with increasing MgCl 2 concentration. 54 Whereas this is likely, we make the case that MgCl 2 is very different from NaCl and not a spacer salt.…”
Section: Introductionmentioning
confidence: 99%